The Impact of Sugar-Sweetened Beverage Taxes on Dental Well-being - Gaushini Ramuvel; Vinay Kumar Bhardwaj; Shailee Fotedar; Shelja Vashisth; Arun Singh Thakur; Atul Sankhyan; Aishwarya Rani Ravichandran (National Board of Examinations Journal of Medical Sciences)
The World Health Organization (WHO) considered it as an effective strategy to reduce sugar consumption. The gradual intake of sugar-sweetened beverages (SSBs) has a significant public health concern, in relation to dental caries, obesity, and other non-communicable diseases (NCDs). Many countries have implemented taxes on sugar-sweetened beverages to reduce their consumption. This review deals with the dual benefits of sugar-sweetened beverages taxes one is by reducing the prevalence of dental diseases and the second by generating revenue for public health initiatives. Certain case studies from countries like Mexico, India, and UK, have shown positive impact of sugar-sweetened beverages taxes on both oral health and economic sustainability. There are some challenges like potential regressive effects and industry opposition, and some of the evidence has shown sugar-sweetened beverages taxes can greatly reduce sugar consumption, enhance public health outcomes, and decline healthcare costs. A few recommendations like allocating tax revenue to oral health education, implementing graduated tax rates based on sugar content, and launching awareness campaigns can help in improving the oral health status of the population. Globally, sugar-sweetened beverages taxes play a promising public health strategy to overcome the rising burden of oral diseases as well as other non-communicable diseases.